함정 간이 취약성 해석 프로그램 개발에 대한 연구 - 신윤호(Yun-Ho Shin); 권정일(Jeong-Il Kwon); 정정훈(Jung-Hoon Chung) (大韓造船學會 論文集, 2013)
Analysis and review of survivability is one of the most important aspects when naval vessels are designed. Because aiming points of threat towards the naval vessels in the battle field could not be estimated exactly, probabilistic and statistic approach is frequently introduced to evaluate and enhance the vessel survivability. Some commercial survivability analysis programs are used to perform the analysis for enhancement of susceptibility, vulnerability and recoverability but, they are usually classified and impossible to be exported to other countries because of their national security. In this paper, a simplified vulnerability analysis program is developed to evaluate the vulnerability of the warship in aspects of structure, redundancy and its mission capability at the conceptual design stage. To verify the developed program, the analysis results were compared with those of the commercial program MOTISS(Measure of Total Integrated System Survivability).